Application of Postoperative Remote Follow-Up of CIED Based on the 5G Cloud Technology Support Platform in Areas With Underdeveloped Medical Resources - Tong, Lin; Long, Yu; Xiong, Shiqiang; Li, Jin; Huang, Wenchao; Liu, Hanxiong; Cai, Lin (Frontiers in Cardiovascular Medicine, 2022)
Postoperative follow-up is crucial for the clinical management of patients carrying cardiovascular implantable electronic devices (CIED). However, in a plethora of underdeveloped areas of China, due to limited medical resources and associated economic costs, geographical restrictions, the outbreak of the COVID-19 pandemic, and various other reasons, the medical system is unable to meet the ever-increasing demand for long-term clinical follow-up and telemedicine services. Based on these challenges, postoperative remote follow-up of CIED based on the 5G-cloud technology support platform (5G-CTP) may have the potential to optimize the allocation of medical resources and provide patients with high-quality CIED follow-up services locally. These unique characteristics of CIED follow-up utilizing 5G-CTP are qualified to protect the safety of the patients in terms of both clinical safety and cyber security. Furthermore, during the COVID-19 pandemic, remote follow-up of CIED significantly reduces the risk of viral exposure to patients and medical staff while having the potential to improve the current situation of CIED postoperative follow-up.